2017
DOI: 10.1209/0295-5075/118/37002
|View full text |Cite
|
Sign up to set email alerts
|

Bulk-sensitive Mo 4d electronic structure of Sr2FeMoO6probed by high-energy Mo L3resonant photoemission

Abstract: We studied the Mo 4d electronic structure of Sr2FeMoO6 using high-energy Mo L3 resonant photoemission. The experimental spectra are in good agreement with modified Becke-Johnson (mBJ) band structure calculations. The energy dependence of the spectra can be explained by the changes in the photoemission cross-sections. The Mo L3 resonant spectrum shows Mo 4d character below the Fermi level and mixed Mo 4d-O 2p character around 8.0 eV. The Mo 4d weight in the resonant spectrum is in good agreement with the calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In MoO 2 , the large value for T is due to the dimerization that occurs between neighboring Mo 4+ ions. Overall, the parameters for RuO 2 and MoO 2 are in good agreement with those reported in similar materials [8,21], but no previous cluster model studies were found for the Rh 2 O 3 compound. Table II presents the main contributions to the ground state of Rh 2 O 3 , RuO 2 , and MoO 2 .…”
Section: B Resonant Photoemissionsupporting
confidence: 87%
See 2 more Smart Citations
“…In MoO 2 , the large value for T is due to the dimerization that occurs between neighboring Mo 4+ ions. Overall, the parameters for RuO 2 and MoO 2 are in good agreement with those reported in similar materials [8,21], but no previous cluster model studies were found for the Rh 2 O 3 compound. Table II presents the main contributions to the ground state of Rh 2 O 3 , RuO 2 , and MoO 2 .…”
Section: B Resonant Photoemissionsupporting
confidence: 87%
“…In principle, it allows one to identify and decompose the O 2p and transition-metal (TM) d partial contributions to the valence band (VB) of a given system, which are usually heavily mixed. The use of high photon energies also gives this method bulk sensitivity, which can be applied to interpret with an excellent agreement several physical properties of these TMO materials [5][6][7][8].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The core level Fe 2p and Mo 3p spectra presented here are new, whereas the valence band spectrum was already presented in a previous study. 21…”
Section: Methodsmentioning
confidence: 99%
“…The energy position and relative intensity of these Mo 4d structures are in agreement with those observed in a recent Mo L 3 resonant photoemission experiment. 21 Although the single cluster model results reproduce the overall shape of the valence band, they fail to explain the magnetic order and the electrical conductivity of the compound. The double cluster model gives an anti-parallel ordering of the Fe 3d 5 and Mo 4d 1 magnetic moments, which is in agreement with the observed ferrimagnetic ordering in Sr 2 FeMoO 6 , whereas the single cluster model produces an independent alignment of the magnetic moments yielding a paramagnetic state.…”
Section: Valence Band Spectroscopymentioning
confidence: 96%